DPsim—A dynamic phasor real-time simulator for power systems - Markus Mirz; Steffen Vogel; Georg Reinke; Antonello Monti (SoftwareX, 2019)
DPsim is a real-time capable solver for power systems that operates in the dynamic phasor and electromagnetic transient (EMT) domain. This solver primarily targets co-simulation applications and large-scale scenarios since dynamic phasors do not require sampling rates as high as EMT simulations do. Due to the frequency shift introduced by the dynamic phasor approach, the sampling rate and rate of data exchange between simulators can be reduced. DPsim supports the Common Information Model (CIM) format for the description of electrical network topology, component parameters and power flow data and it is closely integrated with the VILLASframework to support a wide range of interfaces for co-simulation. Simulation examples demonstrate the accuracy of DPsim and its real-time performance for increasing system sizes. Keywords: Real-time simulation, Dynamic phasors, Co-simulation